Cancer as a Global Health Threat: A Review of Pathogenesis, Prevention, Access to Care and Application of Nanoparticles in Cancer Treatment - Khatlan, Saif al deen M.; Khudhair, Ali Y.; Hamad, Rokan H. (Journal of Science in Medicine and Life, 2025)
One of the main causes of death in the globe is still cancer. Cancer is a disease where abnormal cells grow uncontrollably and can spread, often forming tumors in the body. These tumors can be either cancerous or non-cancerous (benign). Cancerous tumors can invade nearby tissues and spread to distant areas of the body, forming secondary tumors. Traditional cancer therapies, such as chemotherapy and radiotherapy, are associated with significant limitations, including lack of specificity, cytotoxicity, and multidrug resistance, leading to adverse effects and recurrence. Nanotechnology provides particular advantages for cancer treatment. By reducing its adverse effects, it has the potential to reduce systemic toxicity by directing drugs to target cancer cells specifically and creating functionalized particles for targeted treatment. Nanotechnology has emerged as a revolutionary solution in cancer diagnosis and treatment, offering advantages such as biocompatibility, reduced toxicity, and precise targeting of the tumor microenvironment. Nanoparticles, including liposomes, polymers, metallic nanocarriers, and quantum dots, provide improved pharmacokinetics, enhanced drug delivery, and customizable properties for greater therapeutic efficacy. This review explores the pathological and physiological impact of cancer, its types, and complications, with an emphasis on the transformative role of nanoparticles in advancing cancer treatment. This review focused on one of the modern methods used to treat cancer using nanoparticles.